Bioelectric activity of cerebral cortex in patients with cycles of assisted reproductive technologies - A. V. Kaminsky (Kazimierz Wielki University, 2018)
The mental state of patients and, to a greater extent, their psychological and psychoemotional features, have a great influence on fertility and, accordingly, on the result of infertility treatment by assisted reproductive technologies (ART). The aim of the study was to assess the bioelectrical activity of the cerebral cortex on the day of ovulation and the implantation window in the simulation of emotional stress in healthy women and patients in cycles of ART. A total of 64 reproductively healthy fertile patients and 43 female ovulating women with tubal peritoneal infertility were examined and applied for treatment in ART. The recording of the electroencephalogram (EEG) was performed in accordance with the "10-20" system in the frontal, central, occipital, temporal regions on the right and left. The characteristics of the bioelectric activity of the cerebral cortex in groups of women with tubal peritoneal infertility, planning the passage of ART cycles, and stress-unstable fertile women are similar, which is manifested by the absence of differences in the parameters of the dominant and average frequency of the rhythm, the maximum and average amplitude on the 5th-6th day of the menstrual period cycle, the day of ovulation, as well as the growth of dominant activity during the period of the implantation window. The decay of the regular alpha-rhythm, when replaced with a faster beta-activity, combined with a significant increase in vegetative reactivity (especially with respect to the low-frequency component of the spectrum), confirmed during the implantation window, confirms the hypothesis of a particular stressful vulnerability of the 21th-22th day of the menstrual cycle, which is fundamentally important for the successful implantation of blastocyst.